(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
High interest rates operated by financial institutions have been slowing the economic recovery after the last financial crisis. The constant absence of a legal restriction on the interest rates charged by these institutions has allowed them, rather than the public sector, to dictate the direction of the economy. While the Copom is constantly lowering the basic interest rate, Selic, the financial sector has been keeping its interest rates at an intimidating level for raising credit and investing in the productive base. National legislation has gone through a series of attempts to set a ceiling on internally employed interest, including the recent Proposed Amendment to Constitution No. 79 of 2019, which seeks to insert Paragraph 4th in art. 192, of the constitutional diploma. However, previous arguments employed to inutilize and render the former paragraph 3rd of this article, must be transposed. Meanwhile, financial institutions have been maintaining a serious privilege that removes them from restrictions, letting them travel freely and determining the conduct of the national economy.